Assessing Children With Disabilities Using WHO International Classification of Functioning, Disability and Health Child and Youth Version Activities and Participation D Codes. Issue 4 (28th October 2015) - Illum, Niels Ove; Gradel, Kim Oren
Aim: Evaluation of the International Classification of Functioning, Disability and Health child and youth version (ICF-CY) activities and participation d code functions in clinical practice with children across diagnoses, disabilities, ages, and genders. Methods: A set of 57 codes were selected and worded to describe children's support needs in everyday life. Parents of children aged 1 to 15 years participated in interviews to discuss and rate their child's disability. Results: Of 367 invited parents, 332 (90.5%) participated. The mean age of their children with disability was 9.4 years. The mean code scores were 50.67, the corrected code–total correlations were .76, intercode correlations had the mean of 0.61, and Cronbach's α was .98. As a result of Rasch analysis, graphical data for disability measures paralleled clinical expectations across the total population of 332 children. Conclusion: The World Health Organization International Classification of Functioning, Disability and Health child and youth version d code data can provide a coherent measure of severity of disability in children across various diagnoses, ages, and genders.